Mempercepat pertumbuhan UMKM melalui model waralaba dalam perspektif hukum ekonomi syariah - Naufal Fadillah Fadillah (Jurnal Ilmiah Ekonomi Islam, 2023)
Franchising is a popular business model in various industry sectors because it allows entrepreneurs to expand their business quickly through partnerships using established trademarks, products and operational systems. In the perspective of Islamic economic law, franchising with its various advantages has the potential to become an economic instrument that contributes to the development of an economy based on Islamic principles. Several principles in Islamic economics such as profit sharing, prohibition of usury, and avoidance of gharar (uncertainty) are principles that can be applied to franchising activities because they do not contradict general economic principles. This study is a legal study of Islamic economics with a statute approach and interprets existing data and legal documents so as to obtain information that UMKM as businesses with the scope of micro, small and medium which are currently the mainstay of the Government because they are considered able to survive amid the economic crisis can develop quickly because they make franchising a model in doing business.